A Structural Model for the Antecedents of Sustainable Project Management in Pakistan - Ullah, Mehfooz; M., Waris; Lee, Chia Kuang; Hussain, Ammar; Rana, Faisal; Khan, Asadullah; Sajid, Mirza Rizwan (MDPI, 2020)
Sustainable development is the core agenda item of the 21st century to be addressed simultaneously by societies, businesses, and academia. Likewise, sustainability research in the project context is fragmented and still at a nascent stage with less attention directed towards the key antecedents particularly in developing countries. Using institutional theory, this paper analyzes the role of normative and mimetic isomorphic pressures as external enablers for integrating sustainability in project processes. Additionally, it aims to empirically validate a structural model for predictors of sustainable project management (SPM). Data were collected from 146 large construction firms in Pakistan which were then analyzed using the partial least square structural equation modeling (PLS-SEM) technique. The results show that mimetic isomorphic pressures assert more influence than normative pressures in predicting the sustainability performance of construction projects. The inferred implications suggest that large construction firms will tend to improve their sustainable performance under isomorphic pressure from professional bodies and from those competitors who are early adopters of sustainable project practices. This paper contributes to the literature by explaining the role of non-coercive isomorphism as an important enabler of SPM in developing countries. The model presented will enrich our current understanding of SPM by studying its juxtaposition with institutional theory and sustainable development research.